SARANA DAN PRASARANA PENDIDIKAN DASAR DAN PERMASALAHANNYA - Rizki Ananda; Dimas Ardiansyah; Chandra Rinaldi; Selvi Darmayanti; Suci Rahmadhani.S (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The role of facilities or infrastructure in the field of education is to create a pleasant, conducive, and effective learning environment for teachers and students. The condition of facilities and infrastructure in Indonesia is still far from adequate, especially for remote areas. The facilities used in learning can include various things used in learning activities, such as computers, learning media, teaching aids, and so on. While the existence of the infrastructure itself is related to supporting facilities such as sports facilities, toilets, libraries, school rooms, and school buildings. The purpose of this writing is to provide analytical results related to basic education facilities and infrastructure and their problems. The research method used in this writing adopts a qualitative research method. The conclusion drawn through the explanation above is that the problems with facilities or infrastructure include poor physical conditions, distribution inequality, lack of maintenance, lack of modern learning facilities, and limited funds and budget. Based on this, it is necessary to make efforts to improve, including increasing the budget for basic education, involving the community and business world in the development of educational facilities, monitoring and evaluating periodically related to the condition of educational facilities, and evenly distributing assistance for facilities and infrastructure in regions in Indonesia, especially the 3T region.